Speculation (edited) - Memorial University of Newfoundland. Extension Service (MUN Extension Service, 1980)
Prepared for use in a public meeting in the Goulds which met to examine the issue of land speculation and its impact on the farmer. Animation techniques are used to describe the concept of speculation